Corncob formation between Fusobacterium nucleatum and Streptococcus sanguis - P. Lancy; Joseph M. DiRienzo; B Appelbaum; Burton Rosan; Stanley C. Holt (1983)
Corncob formation in dental plaque was believed to be limited to strains of Bacterionema matruchotii and Streptococcus sanguis. We observed recently that strains of Fusobacterium nucleatum also interacted with S. sanguis to form corncobs. Since the fusobacteria are among the first anaerobic filaments to colonize subgingival plaque, these interactions could serve as a connecting link between the transformation of supra- to subgingival plaque. To further characterize these interactions, quantitative in vitro studies of the kinetics of corncob formation of the fusobacteria were undertaken. These studies indicated that fewer streptococci were needed to saturate F. nucleatum strain 364 compared to strain 10953. Corncob formation with both strains was enhanced with increasing pH up to pH 8, at which point autoaggregation of the streptococci occurred. Variation in ionic strength and divalent cations had little effect on the interaction, and EDTA suppressed aggregate formation only slightly. Detergents at concentrations above 0.05% also inhibited corncob formation. Electron micrographs suggested that attachment of the cocci to the fusiforms was mediated through localized tufts of fimbriae, as they are in the Bacterionema system. However, although both trypsin and heat treatment of the streptococci inhibited corncob formation with fusobacteria, the effects were not as complete as those seen in Bacterionema species. Unlike the Bacterionema model, trypsin and heat treatment of the fusobacteria resulted in inhibition of corncob formation. These results suggest that several different receptors may be involved in corncob formation.